2007
DOI: 10.1093/cercor/bhm098
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Focally-Induced Brain Plasticity by Dopamine

Abstract: Dopamine (DA) simultaneously produces both excitation and inhibition in the human cortex. In order to shed light on the functional significance of these seemingly opposing effects, we administered the DA precursor levodopa (L-dopa) to healthy subjects in conjunction with 2 neuroplasticity-inducing motor cortex stimulation protocols. Transcranial direct current stimulation (tDCS) induces cortical excitability enhancement by anodal and depression by cathodal brain polarization, which is not restricted to specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
195
3
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(222 citation statements)
references
References 34 publications
20
195
3
4
Order By: Relevance
“…Moreover, because of the randomized order of conditions, we would not expect a systematic impact of any minor carryover effect on the results. Finally, previous studies of our group in which a similar procedure was performed showed PAS plasticity effects in the placebo medication conditions, which are comparable to the experiments of other groups, in which not such a frequent repetition of sessions was performed (Kuo et al, 2008;Monte-Silva et al, 2009;Monte-Silva et al, 2010;Stefan et al, 2000;Stefan et al, 2004;Thirugnanasambandam et al, 2012). Therefore, late-phase plasticity is unlikely to have compromised the results of the present experiments.…”
Section: General Remarkssupporting
confidence: 89%
See 2 more Smart Citations
“…Moreover, because of the randomized order of conditions, we would not expect a systematic impact of any minor carryover effect on the results. Finally, previous studies of our group in which a similar procedure was performed showed PAS plasticity effects in the placebo medication conditions, which are comparable to the experiments of other groups, in which not such a frequent repetition of sessions was performed (Kuo et al, 2008;Monte-Silva et al, 2009;Monte-Silva et al, 2010;Stefan et al, 2000;Stefan et al, 2004;Thirugnanasambandam et al, 2012). Therefore, late-phase plasticity is unlikely to have compromised the results of the present experiments.…”
Section: General Remarkssupporting
confidence: 89%
“…Accordingly, activation of 5-HT2 receptors has a facilitatory effect on NMDA receptor-dependent LTP induction in the visual cortex of adult rats (Park et al, 2012). Finally, serotonin affects cholinergic (Consolo et al, 1994;Matsumoto et al, 2001;Yamaguchi et al, 1997), GABAergic (Roerig and Katz, 1997;Waider et al, 2012), nicotinergic (Zaniewska et al, 2009), and dopaminergic (Gobert and Millan, 1999;Wood and Wren, 2008) systems, which have a major impact on stimulation-induced plasticity in humans Kuo et al, 2008;Monte-Silva et al, 2009;Monte-Silva et al, 2010;Nitsche et al, 2004;Thirugnanasambandam et al, 2012). While it cannot be ruled out completely that serotonin enhancement affected plasticity partially by its impact on one of these neuromodulatory systems, a profound contribution seems unlikely, because the impact of citalopram on tDCS-, and PAS-induced plasticity differs relevantly from those of other neuromodulators.…”
Section: Proposed Mechanisms Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed there is ample evidence that the somatosensory cortex influences brain DA activity including striatal DA release (Huttunen et al, 2003;Rossini et al, 1995;Chen et al, 2007). There is also evidence that DA modulates the somatosensory cortex in the human brain (Kuo et al, 2007). Inasmuch as DA stimulation signals saliency and facilitates conditioning (Zink et al, 2003, Kelley, 2004), DA's modulation of the somatosensory cortex's response to food is likely to play a role in the formation of conditioned association between food and food-related environmental cues and in the enhanced reinforcing value of food that occurs in obesity (Epstein et al, 2007).…”
Section: Correlation Between D2r and Somatosensory Cortexmentioning
confidence: 99%
“…In the dopaminergic system, levodopa enhances its magnitude and duration (Kuo et al, 2008) but no longer when D2 receptors are blocked by sulpiride ). On the other hand, the D2 receptor agonist ropinirole decreases PASinduced LTP-like plasticity dose dependently in an inverted U-shaped manner ).…”
Section: Introductionmentioning
confidence: 99%